Integrating a 19F MRI Tracer Agent into the Clinical Scale Manufacturing of a T-Cell Immunotherapy. (2nd November 2017) - O'Hanlon, Charles F.; Fedczyna, Tamara; Eaker, Shannon; Shingleton, William D.; Helfer, Brooke M.
Abstract : Leukocyte immunotherapies have made great progress in the treatment of cancer. Recent reports on the treatment of B-cell malignancies using Chimeric Antigen Receptor and affinity enhanced T-Cell Receptor therapies have demonstrated encouraging clinical results. As investigators begin to explore the treatment of solid tumors with these cells, the hurdle of evaluating T-cell homing to and persistence at the site of disease remain. Significant challenges regarding the GMP manufacture and administration of a therapeutic dose of millions to billions of transduced T-cells remain. Here we report on the application of a clinically authorized 19F MRI tracer agent to human T-cells, employing state-of-the-art methods and equipment in the manufacture of a cellular therapy. Using a general T-cell expansion protocol and clinical scale industrial bioreactors, we show 19F labeling without detriment to the product +/− cryopreservation. While the incorporation of the 19F tracer is not trivial, it is just one of the many steps that can aid in progression of a therapeutic to and though the clinic. Combining the MRI tracking capabilities, safety profiles, and clinical sensitivity of this method, this application demonstrates the ability of 19F MRI to be used in industrial scale applications to visualize the spatial fate of cellular therapeutics.